The Effect of Principal’s Leadership and School Culture on Teachers’ Performance in Public Junior High Schools - Resdayani Resdayani; Yasir Arafat; Nurlina Nurlina (Journal of Social Work and Science Education, 2026)
This study aims to examine the effect of school principal leadership and school culture on teacher performance in public junior high schools in Pangkalan Lampam District, Ogan Komering Ilir Regency. The research employed a quantitative approach with a correlational design, involving 83 teachers selected through proportional random sampling from a population of 104 teachers. Data were collected using Likert-scale questionnaires measuring school principal leadership, school culture, and teacher performance, and were analyzed through prerequisite tests (normality, linearity, multicollinearity, and heteroscedasticity) followed by multiple linear regression analysis using t-tests and F-tests at a 5% significance level. The results indicate that school principal leadership has a positive and significant effect on teacher performance, school culture also has a positive and significant effect on teacher performance, and both variables simultaneously exert a significant influence on teacher performance. These findings highlight that effective leadership practices and a strong, positive school culture are key organizational factors in enhancing teacher performance. The novelty of this study lies in its integrated analysis of principal leadership and school culture as joint predictors of teacher performance within the specific context of public junior high schools in Pangkalan Lampam District, providing localized empirical evidence that supports and extends existing theories of educational leadership and organizational culture. From a practical perspective, the findings imply that efforts to improve teacher performance should prioritize strengthening principals’ leadership capacities through continuous professional development and fostering positive school cultures characterized by collaboration, professionalism, and shared responsibility. In terms of contribution, this study enriches the literature on educational management by offering empirical insights into the systemic relationship between leadership, school culture, and teacher performance, and it provides a valuable reference for policymakers, school leaders, and future researchers in designing effective school improvement and leadership development strategies aimed at improving the quality of education.